2002
DOI: 10.1037/0096-3445.131.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy in melody: Tests of children and adults.

Abstract: Melodic expectancies among children and adults were examined. In Experiment 1, adults, 11-year-olds, and 8-year-olds rated how well individual test tones continued fragments of melodies. In Experiment 2, 11-, 8-, and 5-year-olds sang continuations to 2-tone stimuli. Response patterns were analyzed using 2 models of melodic expectancy. Despite having fewer predictor variables, the 2-factor model (E. G. Schellenberg, 1997) equaled or surpassed the implication-realization model (E. Narmour, 1990) in predictive ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 138 publications
(258 reference statements)
5
83
1
Order By: Relevance
“…In both studies, it was found that the model developed by Krumhansl (1995a) provided a much better fit to the data than those of Krumhansl (1995b) and Schellenberg (1996Schellenberg ( , 1997. By contrast, Schellenberg et al (2002) have found the opposite to be true in experiments with adults and infants in a task involving the rating of continuation tones following contexts taken from Acadian (French Canadian) folk songs. They suggest that the difference may be attributable partly to the fact that none of the musical contexts used in the experiments of Krumhansl et al (1999Krumhansl et al ( , 2000 ended in unambiguously large and implicative intervals (Schellenberg et al, 2002, p. 530).…”
Section: The Bottom-up Systemmentioning
confidence: 66%
See 2 more Smart Citations
“…In both studies, it was found that the model developed by Krumhansl (1995a) provided a much better fit to the data than those of Krumhansl (1995b) and Schellenberg (1996Schellenberg ( , 1997. By contrast, Schellenberg et al (2002) have found the opposite to be true in experiments with adults and infants in a task involving the rating of continuation tones following contexts taken from Acadian (French Canadian) folk songs. They suggest that the difference may be attributable partly to the fact that none of the musical contexts used in the experiments of Krumhansl et al (1999Krumhansl et al ( , 2000 ended in unambiguously large and implicative intervals (Schellenberg et al, 2002, p. 530).…”
Section: The Bottom-up Systemmentioning
confidence: 66%
“…They suggest that the difference may be attributable partly to the fact that none of the musical contexts used in the experiments of Krumhansl et al (1999Krumhansl et al ( , 2000 ended in unambiguously large and implicative intervals (Schellenberg et al, 2002, p. 530). While Schellenberg et al (2002) and Krumhansl et al (1999) found strong support for the principle of proximity with only limited influence of registral return and intervallic difference, Krumhansl et al (2000) found the strongest bottom-up influence came from the principle of intervallic difference with weak support for the principles of proximity and registral return. The consonance predictors of Krumhansl (1995a) made a strong contribution to both models especially in the case of the folk hymns (Krumhansl et al, 1999(Krumhansl et al, , 2000.…”
Section: The Bottom-up Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Deutsch (2013) has suggested that these shapes (P*R0P*) may have been laid down in infant development and perhaps derive from the common paralinguistic contours of speech directed toward soothing infants. Other studies conclude instead that reversal is not inborn (Schellenberg, Adachi, Purdy, & McKinnon, 2002) but rather learned (Patel, 2008;Vos & Troost, 1989) as an archetypal schema (stylistically described by Meyer, 1956Meyer, , 1973Meyer, , 1989Meyer, , 2000Narmour, 1990;Rosner & Meyer, 1982.…”
Section: Reversalmentioning
confidence: 99%
“…From this beginning, many experiments based on the I-R model ensued (e.g., Cuddy & Lunney, 1995;Krumhansl, 1991bKrumhansl, , 1995aKrumhansl, , 1995bKrumhansl, , 1997Krumhansl et al, 2000;Pearce & Wiggins, 2006;Schellenberg 1996Schellenberg , 1997Schellenberg et al, 2002;Schmuckler, 1989;Thompson, Balkwill, & Vernescu, 2000;Thompson, Cuddy, & Plaus, 1997;Thompson & Stanton, 1998). For other important studies on melodic implication, see Carlsen (1981), Larson (2004), Margulis (2005), and Unyk and Carlsen (1987).…”
Section: An Analytical Examplementioning
confidence: 99%